Under the Mask: A Film on Tuberculosis at the Thai-Myanmar Border - Delmas, Michele Vincenti; Soan, Mary; Khirikoekkong, Napat; Aung, Ko Ko; Ler Wah, Saw; Htun, Win Pa Pa; Maung, Banyar; Mukaka, Mavuto; Cheah, Phaik Yeong (Frontiers in Public Health, 2022)
In this paper, we describe the development of the film, “Under the Mask,” which follows the lives of three fictional characters who live on the Thai-Myanmar border as they journey from diagnosis of tuberculosis (TB) to completion of treatment. Under the Mask was filmed on location on the Thai-Myanmar border by local filmmakers and former refugee populations. Cast members were chosen from communities living along the border. This paper describes the script development process, filming, and screening in the community. We also report the findings from the pre- and post-screening questionnaires and post-film focus group discussions. A total of 77 screening events took place between March 2019 and March 2020 to 9,510 audience members in community venues such as village squares, temples and monasteries (N = 21), schools/migrant learning centers (N = 49), and clinics (N = 4). The pre-and post-screen questionnaires showed a significant gain in self-perceived TB knowledge on prevention, transmission, signs and symptoms, and related discrimination. Our findings from 18 post-screening focus group discussions conducted with 188 participants showed that there were improvements in knowledge and awareness of the disease and treatment, as well as in the awareness of stigma, and the burdens of tuberculosis on patients and their families.